PENGEMBANGAN EVALUASI PEMBELAJARAN MENGGUNAKAN EDUCAPLAY PADA TOPIK POLA HIDUP GOTONG ROYONG - Chintia Yuniar Rahayu; Nita Karmila; Ade Wijaya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is a type of Research and Development (R&D) employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), aimed at developing a learning evaluation tool using Educaplay on the topic of Cooperative Living Patterns. The study was conducted at SD Pertiwi, Bogor City, with 32 fourth-grade students during the even semester of the 2024/2025 academic year. The validity test was carried out by media experts, a language expert, and two subject matter experts. In addition to expert assessments, questionnaires were distributed to students and teachers to further develop and refine the learning evaluation tool using Educaplay. The validation results showed that media experts rated it at 92% (Very Feasible), the language expert at 98% (Very Feasible), the subject matter expert (lecturer) at 88% (Very Feasible), and the subject matter expert (teacher) at 80% (Very Feasible). The student response questionnaire yielded a score of 88% (Very Feasible), while the teacher response reached 90% (Very Feasible). Based on these results, it can be concluded that the learning evaluation developed using Educaplay is suitable for use by elementary school students in classroom learning activities.